(untitled) (The Review of Diabetic Studies, 2025)
HR practices with high performance work systems are those approaches of management which integrate different sets of workforce practices to revamp the execution of business. The previous studies favour HR management practices, modern HR management, and progressive HR management. HPHR Practices differ from traditional human resource practices (Jyoti et al., 2017). Looise& Paauwe, (1998) elaborated that in the area of HRM, all facets dealing with a personnel matter are encompassed in the function. According to the elaboration of Guest et al., (2012) HPWS was determined by accounting profits, the market value of the organization, and turnover within the organization. This article concentrates on assess the influence of present organization experience of the respondents on high performance human resource practices. The researcher used Anova analysis to find the result of the research study. The findings suggest that employees with fewer years in their present organization tend to rate high-performance HR practices more favorably than those with longer tenure. Employees with more than 10 years of experience consistently reported the lowest mean scores across all six HR practices, indicating potential dissatisfaction or declining perceived relevance of these practices over time.